PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN MOTIVASI TERHADAP ORGANISATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT. BANK CENTRAL ASIA KANTOR CABANG UTAMA YOGYAKARTA - MOHAMMAD ILHAM (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose this study was to describe (1) the effect of LMX (Leader Member Exchange) on OCB (Organization Citizenship Behavior), the influence of motivation on OCB (Organization Citizenship Behavior) and (3) the effect of LMX (Leader Member Exchange) dan motivation on OCB (Organization Citizenship Behavior) PT. Bank Central Asia Kantor Cabang Utama Yogyakarta. This study classified as an associative research. Variable of this study are LMX (Leader Member Exchange) (X1), Motivation (X2) and OCB (Organization Citizenship Behavior) (Y). The population are 345 employess of PT. Bank Central Asia Kantor Cabang Utama Yogyakarta. and used 185 employess as the sample. Data colletion using questionare with probaility sampling with aksidental sampling method. This study used multiple regresion analys by the F-test and T-test and the classical assumption tes are normality test, multicollinearity test and heteroscedasticity. The result showed: (1) there is positive and significant correlation between LMX (Leader Member Exchange) and OCB (Organization Citizenship Behavior) the result of regression are β=0.121 and sig. 0.020 (0.020<0,05), (2) there is positive and significant correlation between motivation and OCB (Organization Citizenship Behavior) with β=1.254 sig. 0.000 (0,000<0.05). Value of coefficient determination (R2) is equal to 0.475 or 47,5% mean OCB variable influenced by LMX (Leader Member Exchange) and motivation the different are influenced by another factor.